Efek Dua Sediaan Ramuan Jamu pada Pasien Obesitas: Studi Klinis dengan Desain Paralel, Random dan Tidak Tersamar - Zulkarnain, Zuraida; Nisa, Ulfatun; Wijayanti, Enggar; Fitriani, Ulfa (Jurnal Kefarmasian Indonesia, 2019)
Obesity is a co-morbidity of cardiovascular disease, diabetes, and other metabolic diseases, which the prevalence increases every year. The use of herbal medicine is an alternative choice to overcome obesity. Clinical observation of decoction of herbal medicine (Dutch teak, kemuning, rhei radix and tempuyung) has been conducted for obesity therapy which has been proven to be effective in reducing body weight and body mass index (BMI). Innovation in steeping form is considered more practical than stew. Randomized open label pararel design research was carried out to assess the equal efficacy of the herbs in stew and steeping form. The number of subjects in each group were 30 subjects, they were patients of of Rumah Riset Jamu (RRJ) Hortus Medicus during June-October 2016 who met the inclusion criteria. BW and BMI are measured on Day-0, 28 and 56, while body height is measured once at Day-0. Both stew and steeping groups drank herbs twice a day for 56 days. At the end of the study, it was found that the mean of declining BW of the decoction group was 67.35 kg to 66.37 kg, while the steeping group 67.41 kg to 66.45 kg. BMI of stew group was decreased 26.85 kg / m2 to 26.46 kg / m2, while in steeping group 26.67 kg / m2 to 26.29 kg / m2. Statistic test result to compare BW and BMI of both two groups before and after treatment showed no significant differences in the two groups (p> 0.05). The ability of herbal medicines in steeping or stew forms can reduce the BW and BMI equally.